Molecules at Play in Cancer (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
"Molecules at Play in Cancer" is a collection of 24 research articles on recent findings about some important molecules responsible for either cancer development and proliferation, or anti-cancer therapy. It covers a wide range of tissues and organs affected by cancer: adrenal glands, blood, breasts, muscles, ovaries, prostate, stomach, and testicles.